2011
DOI: 10.5551/jat.7229
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Lower-Body Fat Mass with Favorable Profile of Lipoproteins and Adipokines in Healthy, Slim Women in Early Adulthood

Abstract: Aim:We determined the association of lower-body fat mass (LFM) and trunk fat mass (TFM) with cardiometabolic risk factors and adipokines in young, healthy, slim women. Methods: A total of 481 college female students underwent the following: regional body fat distribution as assessed by dual energy X-ray absorptiometry (DXA), a 75g oral glucose tolerance test (OGTT) and fasting blood sampling for measurement of lipids, lipoproteins, apolipoproteins (apo), liver enzymes and adipokines. Results: After adjusting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 48 publications
(50 reference statements)
3
34
0
Order By: Relevance
“…In the present study, genotype AA was related to abdominal adiposity in middle-aged mothers but not in young women. Waist circumference, intra-abdominal and trunk fat are positively 17,[26][27][28] , whereas lowerbody fat is negatively associated with cardiometabolic risk factors 17,27,28) . In the current study, as compared to young women, middle-aged mothers had a greater amount of trunk fat but a similar amount of lowerbody fat (Table 1), confirming the adverse effects of central or abdominal fat accumulation on cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, genotype AA was related to abdominal adiposity in middle-aged mothers but not in young women. Waist circumference, intra-abdominal and trunk fat are positively 17,[26][27][28] , whereas lowerbody fat is negatively associated with cardiometabolic risk factors 17,27,28) . In the current study, as compared to young women, middle-aged mothers had a greater amount of trunk fat but a similar amount of lowerbody fat (Table 1), confirming the adverse effects of central or abdominal fat accumulation on cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the students and mothers were described in detail elsewhere 17,18) . Genomic DNA was available in 454 out of 481 students and 132 out of 148 mothers.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These symptoms usually accompany emotional problems. Previous studies reported risks of cardiovascular disease [20] and metabolic syndrome [7]. In a domestic study, 30% of body fat was estimated as a risk point of cardiovascular disease for women [21].…”
Section: Discussionmentioning
confidence: 99%